Persepsi Keadilan Pajak sebagai Faktor Moderasi antara Persepsi Tarif Final dan Minat Membayar Pajak UMKM - I Nyoman Sunarta; Komang Trisna Ning Padmawati (Journal of Innovative and Creativity, 2026)
This study addresses the perception of final tax rates and tax fairness as factors influencing MSMEs' willingness to pay taxes. The purpose is to empirically examine the moderating role of tax fairness perception on the relationship between final tax rate perception and tax payment intention. Using a quantitative correlational descriptive approach, data were collected from 355 purposively sampled active university students in Central Java Indonesia. A validated Likert scale questionnaire was employed, and data were analyzed with descriptive statistics and multiple linear regression utilizing SEM-PLS. Results show that perception of the final tax rate positively and significantly influences tax payment intention. However, tax fairness perception did not significantly moderate this relationship. These findings highlight the important role of tax rate perception in encouraging compliance but suggest further investigation into tax fairness as a moderating factor. The study concludes that simple, transparent, and preferential tax rate policies increase MSMEs’ willingness to pay taxes. Further research is recommended with mixed methods and broader samples. Governments are encouraged to enhance transparency, fairness, and simplicity in tax policies to improve voluntary compliance.